Geometry of 2x2 matrix curves - León, Victor (2022)
In this work, we study the geometry of 2x2 order matrix curves with real coefficients. We use the Gram-Schmidt orthogonalization process to generate a convenient moving benchmark. Thus, we obtain the Frenet-Serret formulas. We present a version of the fundamental theorem of 2x2 matrix curves.